(Irmédi-)Molnár László fényképei. (Fond 165 Irmédi-Molnár László)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Személyi iratok: > Irmédi-Molnár László egyet. tanár (1895–1971) hivatalos iratai